1999
DOI: 10.1128/aem.65.10.4334-4339.1999
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Xanthobaccins Produced by Stenotrophomonas sp. Strain SB-K88 in Suppression of Sugar Beet Damping-Off Disease

Abstract: Three antifungal compounds, designated xanthobaccins A, B, and C, were isolated from the culture fluid of Stenotrophomonassp. strain SB-K88, a rhizobacterium of sugar beet that suppresses damping-off disease. Production of xanthobaccin A in culture media was compared with the disease suppression activities of strain SB-K88 and less suppressive strains that were obtained by subculturing. Strain SB-K88 was applied to sugar beet seeds, and production of xanthobaccin A in the rhizosphere of seedlings was confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(63 citation statements)
references
References 21 publications
0
60
0
Order By: Relevance
“…Previous studies have shown that other Lysobacter strains control soilborne plant pathogenic oomycetes such as Aphanomyces cochlioides and Py. aphanidermatum (Nakayama et al 1999;Folman et al 2001Folman et al , 2003Folman et al , 2004Islam et al 2005;). Recently, Ko et al (2009) demonstrated that L. antibioticus HS124 effectively protects pepper plants against P. capsici attacks and linked this activity with the production of lytic enzymes (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that other Lysobacter strains control soilborne plant pathogenic oomycetes such as Aphanomyces cochlioides and Py. aphanidermatum (Nakayama et al 1999;Folman et al 2001Folman et al , 2003Folman et al , 2004Islam et al 2005;). Recently, Ko et al (2009) demonstrated that L. antibioticus HS124 effectively protects pepper plants against P. capsici attacks and linked this activity with the production of lytic enzymes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence that a Lysobacter member produces secondary metabolites with anti-oomycete activity is also corroborated by previous studies carried out on Lysobacter sp. SB-K88, L. antibioticus HS124 and L. capsici YC5194 (Homma et al 1993;Nakayama et al 1999;Islam et al 2005;Park et al 2008;Ko et al 2009). In particular, Lysobacter sp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations